Collating and validating indigenous and local knowledge to apply multiple knowledge systems to an environmental challenge: A case-study of pollinators in India. (July 2017) - Smith, Barbara M; Chakrabarti, Priyadarshini; Chatterjee, Arnob; Chatterjee, Soumik; Dey, Uday Kumar; Dicks, Lynn V; Giri, Bhagirath; Laha, Supratim; Majhi, Rabindra Kumar; Basu, Parthiba
Abstract: There is an important role for indigenous and local knowledge in a Multiple Evidence Base to make decisions about the use of biodiversity and its management. This is important both to ensure that the knowledge base is complete (comprising both scientific and local knowledge) and to facilitate participation in the decision making process. We present a novel method to gather evidence in which we used a peer-to-peer validation process among farmers that we suggest is analogous to scientific peer review. We used a case-study approach to trial the process focussing on pollinator decline in India. Pollinator decline is a critical challenge for which there is a growing evidence base, however, this is not the case world–wide. In the state of Orissa, India, there are no validated scientific studies that record historical pollinator abundance, therefore local knowledge can contribute substantially and may indeed be the principle component of the available knowledge base. Our aim was to collate and validate local knowledge in preparation for integration with scientific knowledge from other regions, for the purpose of producing a Multiple Evidence Base to develop conservation strategies for pollinators. Farmers reported that vegetable crop yields were declining in many areas of Orissa and that the abundance of important insect crop pollinators has declined sharply across the study area in the last 10–25 years, particularly Apis cerana, Amegilla sp. and Xylocopa sp. Key pollinators for commonly grown crops were identified; both Apis cerana and Xylocopa sp. were ranked highly as pollinators by farmer participants. Crop yield declines were attributed to soil quality, water management, pests, climate change, overuse of chemical inputs and lack of agronomic expertise. Pollinator declines were attributed to the quantity and number of pesticides used. Farmers suggested that fewer pesticides, more natural habitat and the introduction of hives would support pollinator populations. This process of knowledge creation was supported by participants, which led to this paper being co-authored by both scientists and farmers. Highlights: A new method for validating indigenous and local knowledge was tested. Local knowledge on changes in vegetable crop yields and pollinator abundance was collated. Declines in both pollinators and crop yields in Orissa, India were reported. The only available information on pollinator declines in Orissa is presented. There is an urgent need for pollinator conservation.